Association of Proton Pump Inhibitor with Hypomagnesaemia: A Cross-Sectional Study at a Tertiary Care Hospital of Anand District - U S, Dunkin; D S, Punam (Indian Journal of Pharmacy Practice)
Proton pump inhibitors (PPIs) are one of the most commonly used class of drugs for gastroesophageal reflux disease and number of other common persistent conditions. Hence, risk of potential long-term side effects associated with the use of PPIs is increasing. On March 2, 2011, the US FDA informed the public of the risk of hypomagnesaemia associated with prolonged usage of PPIs. Hence, the present study was undertaken to estimate the risk of development of hypomagnesaemia in patients who have been treatment with PPIs for at least one month and to check whether PPI induced hypomagnesaemia is a long term side effect with all PPIs. General demographic data, type of PPI used along with its duration of use and dose, morbid conditions, concomitant illness and several other confounders available from the basic metabolic panel of 60 patients (30 long term PPI users and 30 non PPI users), was collected and documented using a structured questionnaire. Serum magnesium levels of all 60 patients were estimated and data collected was analysed using T-test and ANOVA. Users on PPIs and non users had a mean serum magnesium level of 1.848 ± 0.023 mg/dL and 2.167 ± 0.34 mg/dL respectively, with the difference being statistically significant (p=0.00) and was independent of age, gender and concomitant drugs prescribed. However female PPI users had slightly lower serum Mg levels. Of the 30 recruited PPI users, 4 were asymptomatic hypomagnesaemic (serum Mg levels<1.7 mg/dL). Mean serum Mg levels in esomeprazole users were slightly higher than those on omeprazole or pantoprazole, with a statistically insignificant difference.
Keywords: Proton pumps inhibitors; Hypomagnesaemia; Omeprazole; Serum magnesium